The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1439-0329.1998.tb01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of different provenances of Pinus sylvestris, Pinus Contorta and Picea abies to Gremmeniella abietina

Abstract: In a randomized block factorial experiment, 1200 seedlings from four provenances, each of Pinus sylvestris, Pinus eontorta and Picea abies were inoculated with conidia (2 x lO'' and 1 x 10'' conidia/seedling) of Gremmeniella abietina {Bruncborstia pinea), isolated from P. eontorta plantations in northern Sweden. A further 600 seedlings were left as controls. The occurrence of symptoms and the extension of dead tissues on the annual shoots were recorded 13 months after inoculation. Only the higher spore dose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
6
23
1
Order By: Relevance
“…However, infected P. contorta seedlings seemed more resistant in terms of survival rate, length of infected tissue, and recovery by production of new leaders. This is in accordance with earlier inoculation studies conducted in Britain (probably LTT) (Aitken 1993) and Sweden (STT) (Hansson 1998). In Hansson (1998), in situ inoculations caused significantly higher mortality and infection severity on P. sylvestris seedlings compared with P. contorta seedlings, even though the proportion of infected seedlings was equal between the two species.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, infected P. contorta seedlings seemed more resistant in terms of survival rate, length of infected tissue, and recovery by production of new leaders. This is in accordance with earlier inoculation studies conducted in Britain (probably LTT) (Aitken 1993) and Sweden (STT) (Hansson 1998). In Hansson (1998), in situ inoculations caused significantly higher mortality and infection severity on P. sylvestris seedlings compared with P. contorta seedlings, even though the proportion of infected seedlings was equal between the two species.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with earlier inoculation studies conducted in Britain (probably LTT) (Aitken 1993) and Sweden (STT) (Hansson 1998). In Hansson (1998), in situ inoculations caused significantly higher mortality and infection severity on P. sylvestris seedlings compared with P. contorta seedlings, even though the proportion of infected seedlings was equal between the two species. The results in Hansson (1998) were surprising because field trials with pines 2-4 m in height (Hansson and Karlman 1997) and large-scale monitoring of pine plantations in northern Sweden with saplings 1-3 m in height (Karlman et al 1994) had found P. contorta to be more susceptible than P. sylvestris to STT G. abietina in terms of infection and mortality rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Susceptibility of conifers to G. abietina is to some degree under genetic control of the host (Roll-Hansen, 1972;Nevalainen and Uotila, 1984;Stephan et al 1984;Dietrichson and Solheim, 1987;Aitken, 1993;Hansson 1998;Sonesson et al, 2007). However, the role of environmental factors in disease development is essential; severe epidemics occur exclusively under environmental conditions which both predispose the host and favour the spread and survival of the fungus (Donaubauer, 1972;Petäistö and Kurkela, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For other forest trees, considerable amount of research in this range was performed on elms in reference to Ophiostoma novo-ulmi Brasier (Santini et al 2005) and on pines and spruces towards Gremmeniella abietina (Lagerb.) M. Morelet (Roll-Hansen 1971;Hansson 1998), and also inter alia to Cenangium ferruginosum Fr. (Kuzmina, Kuzmin 2008).…”
Section: Introductionmentioning
confidence: 99%